Solutions around a regular a singular point of a sequential conformable fractional differential equation - Unal, Emrah; Gokdogan, Ahmet; Celik, Ercan (Kuwait Journal of Science, 2017)
In this work, firstly, some concepts of conformable fractional calculus in literature are given. Secondly, definitionsof ?-analytic point, ?-ordinary point and regular ? singular point are presented. Finally, the fractional power series solutions are given around a regular-singular point, in the case of variable coefficients for homogeneous sequential linear conformable fractional differential equations of order 2?.